2006
DOI: 10.1179/crn.2006.029
|View full text |Cite
|
Sign up to set email alerts
|

Predisposition for Temporomandibular Joint Disorders: Loose Ligaments

Abstract: Loose ligaments are often a predisposing factor of temporomandibular joint (TMJ) disorders. This causal factor was analyzed in 701 subjects presenting at the TMJ and Posture Center of Siena University with TMJ pain or dysfunction. Along with the conventional jaw examination, a Carter and Wilkinson test as modified by Beighton was also done. We found a correlation among the parameters of age, gender, TMJ disorder, joint pain, muscle pain, and loose ligaments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
0
10
1
7
Order By: Relevance
“…The incidence of TMJ hypermobility has been reported to be greater in women [4], but this has not been substantiated by this study. The incidence of craniofacial pain conditions is also greater in women [15,19].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The incidence of TMJ hypermobility has been reported to be greater in women [4], but this has not been substantiated by this study. The incidence of craniofacial pain conditions is also greater in women [15,19].…”
Section: Discussioncontrasting
confidence: 72%
“…TMJ hypermobility was diagnosed and defined as when the "TMJ condyle overrides joint tubercle making the dull click typical of subluxation" (23.4% were so defined), while GJH was determined by the Carter-Wilkinson test as modified by Beighton [4]. It was concluded that those subjects with TMJ disorders and TMJ hypermobility both had a higher probability of GJH.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile there is a stabilizing force produced by the masseter and temporalis, which with a steeper eminence, places a greater relative distalizing force relative to the disc (Atkinson & Bates, 1983;Isberg & Westesson, 1998). This might result in laxity of the ligaments that attach the disc to the condyle (Perrini et al, 1997;Deodato et al, 2006). The disc articulating against a steep eminence during mouth opening would gradually achieve a more anterior position relative to the condyle, predisposing the disc to anterior displacement (Isberg & Westesson).…”
Section: Resultsmentioning
confidence: 99%
“…The GJH was assessed by the Carter and Wilkinson's criteria, modified by Beighton 29 , which have been used in numerous studies 4,6,[11][12][13][14][15][16] about hypermobility. Beighton's score assesses 9 joints by means of 5 tests: passive thumb opposition to the anterior portion of the forearm, until they touch; passive dorsiflexion of the little finger until it comes parallel to the forearm; elbow and knee hyperextension higher than 10 degrees; trunk flexion with the knees completely extended, in such a way that the palms of the hands touch the floor (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…There are reports that this syndrome is more prevalent in women and in individuals of Asian and African descent, and it reduces with aging 8,9 . GJH has been associated with the development of signs and symptoms of TMD [4][5][6][10][11][12][13][14][15][16] . It is known that although the TMJ is among hypermobile joints, it may predispose some patients to subluxation, although not necessarily with pain or dysfunction 4 .…”
Section: Introductionmentioning
confidence: 99%